Alkaline-earth metal compounds oddities and applications - Harder, Sjoerd (Topics in Organometallic Chemistry, 2013)
Ana Torvisco, Karin Ruhlandt-Senge: Heavy Alkaline-Earth Metal Organometallic and Metal Organic Chemistry: Synthetic Methods and Properties.- Matthias Westerhausen, Jens Langer, Sven Krieck, Reinald Fischer, Helmar Görls, Mathias Köhler: Heavier Group 2 Grignard Reagents of the Type Aryl-Ae(L)n-X (Post-Grignard Reagents.- Cameron Jones, Andreas Stasch: Stable Molecular Magnesium(I) Dimers: A Fundamentally Appealing yet Synthetically Versatile Compound Class.- Robert E. Mulvey, Stuart D. Robertson: Modern Developments in Magnesium Reagent Chemistry for Synthesis.- Jean-François Carpentier, Yann Sarazin: Alkaline-Earth Metal Complexes in Homogeneous Polymerization Catalysis.- Mark R. Crimmin, Michael S. Hill: Homogeneous Catalysis with Organometallic Complexes of Group 2.- Tetsu Tsubogo, Yasuhiro Yamashita, Shū Kobayashi: Chiral Ca, Sr and Ba-catalyzed asymmetric direct-type aldol, Michael, and Mannich and related reactions.